Study of multiple frequency-offset and channel joint ML estimation over virtual multi-antennas OFDM system - JIANG Jian; JIANG Hua; YAN Kai; LIU Hai-tao (Tongxin xuebao)
A pilot-aided joint estimation of the carrier frequency offsets（CFO） and channels of a virtual multi-anten-nas（VMA） orthogonal frequency-division multiple（OFDM） system was considered.For a VMA-OFDM system,each pair of transmit and receive antennas possibly having a different CFO and CIR（channel impulse response） parameters made the parameters joint estimation a challenge task.By utilizing the series expansion of the matrix inversion and maximum likelihood（ML） criterion,a computationally efficient estimator allowing for simultaneously estimating the unknown pa-rameters was developed.The mean square-error（MSE） performance of the interested parameters for the proposed estima-tor was compared with the Cramer-Rao bound（CRB）.In addition,the pilot sequence design was investigated by analysis and simulations.Simulation results show that the proposed low-complexity estimator asymptotically achieves the CRB and overcomes the drawbacks of existing estimators.